Desain IMC - PID untuk kontrol tegangan pada DC - DC Buck Converter - Naufal Maulana Fahmi; Rifqi Firmansyah (JURNAL TEKNIK ELEKTRO, 2026)
Voltage control in DC–DC converters, especially buck converters, is a crucial element in modern power electronics systems because it directly impacts the efficiency, stability, and quality of supply in low- to medium-power electronic devices and industrial applications. Recent studies have emphasized that the nonlinear and load-dependent dynamics of converters require control strategies capable of maintaining stability despite parameter variations and external disturbances. PID-based control methods remain the most widely used approach due to their ease of implementation and ability to handle transient responses, although improper parameter tuning often leads to overshoot and slow response in power converter systems. This challenge is increasingly apparent in buck converters, which have fast dynamics and high sensitivity to load changes, making conventional tuning sometimes inadequate. Internal Model Control (IMC) is one of the modern tuning methods that offers a solution due to its model-based approach and its ability to produce control parameters that are more robust to system uncertainty. This study specifically analyzes the application of the IMC-PID method in buck converters by utilizing the FOPDT model to obtain the , , and  parameters. This approach is expected to provide more stable, faster, and adaptive tuning results compared to conventional methods. Keywords: IMC, PID, buck converter, voltage control.